Trends in Maternal Health Indicators in Colombia: A Systematic Review - Osorio, Edith del Carmen Soto; Caraballo, Álvaro Antonio Sánchez (Journal of Posthumanism, 2025)
The article examines the state of maternal health in Colombia. Maternal health is a critical public health challenge globally, and Colombia has committed to improving these indicators to reduce the maternal mortality ratio (MMR) to less than 70 deaths per 100,000 live births by 20301. The review highlights the increase in MMR in Latin America and the Caribbean by 46.9% by 20212. Prenatal care coverage in the Americas has been stable at 90.7%, but some countries have lower coverage. In Colombia, significant changes in maternal health indicators have been observed since the enactment of Law 100 of 19934. Despite progress, barriers at all levels of care negatively impact health outcomes. The General System of Social Security in Health (SGSSS) reform aimed at universal health coverage has not fully translated into effective accessibility6. Colombia has implemented various plans and resolutions to reduce maternal morbidity and mortality. The objective of this review is to document scientific evidence related to trends in maternal health indicators in Colombia after the SGSSS reform. The review includes studies from various databases and languages, focusing on prenatal care coverage, delivery care coverage, and maternal mortality ratio. Ethical considerations were adhered to throughout the review process.